Diagnosis of cardiomyopathy in domestic dogs - Zarytskyi, S. (Scientific Progress & Innovations, 2023)
The article describes the methods of diagnosis and the results of the study of domestic dogs with cardiomyopathy. In addition to the generally accepted diagnostic methods, special attention was paid to special research methods, namely chest radiography and calculation of the cardiovertebral index, which is an indicator of heart size and echocardiography. These methods are non-invasive and allow for early diagnosis. Chest X-ray allows to visualize and evaluate the shape, size and contour of the heart, the presence of pulmonary edema, which are often signs of cardiovascular disease. Echocardiography allows us to examine the structure of the heart, ventricular walls, valves, and aorta, measure the size of the chambers and assess the ejection fraction and contractions, and identify arrhythmias. These are the two methods we chose to diagnose cardiomyopathy, but we should not forget about other additional diagnostic methods, such as electrocardiography and blood chemistry. The objects of our study were domestic dogs of the boxer, Doberman, Labrador retriever and German shepherd breeds. According to the literature, cardiomyopathy is most often recorded in these breeds due to breed predisposition. The breeds were divided into two groups: clinically healthy and experimental. The results of the cardiovertebral index calculation showed that in experimental animals of the Doberman and German Shepherd breeds, the index exceeded the index of clinically healthy animals by 22.8 % and 21.4 %, respectively. In boxers and Labrador retrievers, this figure was 20.1 and 18.1 % compared to clinically healthy animals. An increase in these indicators indicated myocardial dilation. The next step was to determine changes in the structure of the heart using echocardiography in M-mode. According to the results of echocardiography and indicators, it was found that domestic dogs of the Labrador Retriever and German Shepherd breeds of the experimental group had the most reliable values (p<0.001) in all indicators compared to the clinically healthy group.